Defining aspects of Mesenteric Lymphadenitis: A rare and underexplored condition (Research, Society and Development, 2024)
Introduction: Mesenteric lymphadenitis (ML) is a syndrome characterized by right lower quadrant abdominal pain resulting from an inflammatory condition of the mesenteric lymph nodes. It is a rare and self-limiting condition that generally does not present complications, but it mimics other conditions such as acute appendicitis. Objective: To define general information about mesenteric lymphadenitis. Materials and Methods: This study is an integrative literature review on the general clinical characteristics of mesenteric lymphadenitis and its approaches. The PICO strategy was used to formulate a guiding question. Moreover, a search was conducted using the keywords "Mesenteric Lymphadenitis"; "Clinical Manifestations"; "Propaedeutics," across databases including the National Library of Medicine (PubMed MEDLINE), Scientific Electronic Library Online (SCIELO), Ebscohost, Google Scholar, and Virtual Health Library (BVS). Results and Discussion: Evidence on ML is extremely limited, making it difficult to identify the epidemiological pattern and other defining characteristics of the disease. The peak incidence appears to be between 5 and 8 years old. Abdominal pain, nausea, vomiting, and fever constitute the clinical picture. Lymphocytosis is frequently observed. Complications have not been documented, and the prognosis is generally favorable, with resolution in an average of four weeks. Conclusion: Due to the rarity of mesenteric lymphadenitis, its self-limiting nature, and the scarcity of publications dedicated exclusively to the topic, it is still challenging to precisely delineate the clinical and laboratory patterns that define this condition. Rigorous studies are essential to improve understanding and treatment of mesenteric lymphadenitis.